Anisotropic inverse Compton scattering in radio galaxies and the particle energy distribution - Brunetti, G; Setti, G (2002)
We briefly review the inverse-Compton (IC) scattering of nuclear photons in the lobes of radio galaxies and quasars. We concentrate on the possibility of testing this model with the Chandra observatory and of constraining the electron energy distribution by measuring the Xray fluxes produced by this effect. We also discuss the evidence for IC scattering of nuclear photons in powerful radio galaxies.